Morality, Religion and Capitalism in Jane Austen’s ‘Pride and Prejudice’ - Priydarshi, Ashok Kumar (International Journal of Advanced Research in Peace, Harmony and Education; Vol 5 (2020): International Journal of Advance Research in Peace, Harmony and Education, 2020)
The rise and development of English novels, like any other phenomenon in literature, can be seen as a part of history or the process of individual development. Romantic novels are non-realistic and considered as the aristocratic literature of feudalism. They are non-realistic in the sense that their underlying intention is not to help people cope in a positive way. These novels, express and recommend the attitudes of the aristocratic class to which it was ideally supposed to sustain. The genre, developed, however, as a reaction to the aristocratic romance, and grows with the middle class a new art form that centres on new middle-class values, rather than aristocratic patronage. Thus the period after the Restoration of the 16 th to 17 th century opened up other discourses, thereby breaking the frontier by allowing social mobility and making female writing possible. This allowed Jane Austen to write on realistic and naturalistic themes as morality, religion, capitalism, etc. and ‘Pride and Prejudice’ is its fine example. How to cite this article:  Priydarshi AK. Morality, Religion and Capitalism in Jane Austen’s ‘Pride and Prejudice’. Int J Adv Res Peace Harm Edu 2020; 5: 4-6. DOI: https://doi.org/10.24321/2455.9326.202002